2023
DOI: 10.1002/adma.202304074
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Blinking Luminescence from Charged Single Graphene Quantum Dots

Abstract: Photoluminescence blinking behaviour from single quantum dots under steady illumination is an important but controversial topic. Its occurrence has impeded the use of single quantum dots in bio‐imaging. Different mechanisms have been proposed to account for it, although controversial, the most important of which is the non‐radiative Auger recombination mechanism whereby photo‐charging of quantum dots can lead to the blinking phenomenon. Here, the singly charged trion, which maintains photon emission, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…90,109 GQDs’ π–π conjugated system is the intrinsic cause of their blue PL emission. 110,111 Therefore, the reduction, which removes functional groups like epoxide groups from the lattice of GQDs, leads to improved crystallinity and higher QY. Thirdly, avoiding aggregation of GQDs is crucial.…”
Section: Properties Of Gqdsmentioning
confidence: 99%
See 1 more Smart Citation
“…90,109 GQDs’ π–π conjugated system is the intrinsic cause of their blue PL emission. 110,111 Therefore, the reduction, which removes functional groups like epoxide groups from the lattice of GQDs, leads to improved crystallinity and higher QY. Thirdly, avoiding aggregation of GQDs is crucial.…”
Section: Properties Of Gqdsmentioning
confidence: 99%
“…For instance, a recent study by Fu et al contributes to the understanding of non-blinking luminescence in single GQDs. 111 Furthermore, recent literature includes studies on the synthesis and applications of chiral GQDs, as well as investigations into the layered structures of GQDs. 240,365–367…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Recently, Cui and Xue reported that during the oxidation of epoxy group, the ortho structure exhibited a faster non-radical decay rate compared to the meta structure [159]. Furthermore, Fu et al discussed the PL blinking phenomenon of GQDs through a non-radiative Auger recombination mechanism [160]. In another recent study, Belko et al demonstrated the potential use of GQDs' blinking in super resolution fluctuation imaging (SOFI) as controlled fluorophores [161].…”
Section: Photoluminescence Properties Of Gqdsmentioning
confidence: 99%
“…Firstly, eliminating functional groups for increasing crystallinity of GQDs can enhance QY. The π-π conjugated system within GQDs is responsible for blue PL emission [160,162]. Consequently, the removal of functional groups, such as epoxy groups within the GQDs' graphene lattice through reduction processes, enhances crystallinity and QY [51,143].…”
Section: Photoluminescence Properties Of Gqdsmentioning
confidence: 99%
“…Hence, the wavelength-dependent emission intensity was attributed to the selective excitation and recombination of neutral excitons and defect-bound excitons at different excitation wavelengths as well as to the size distribution of QDs. 56,91 We have found the maximum intensity for an excitation wavelength of 400 nm, and hence we have used a 405 nm laser excitation for further FL measurements. The quantum yield (QY) of the synthesized WS 2 QDs was measured with 330 nm excitation at a low concentration of 1 μg mL −1 and the obtained QY was 52.1%, the highest reported to date.…”
Section: Compositional and Structural Characterizationmentioning
confidence: 99%